TAPB and RSB protects cardiac diastolic function in elderly patients undergoing abdominopelvic surgery: a retrospective cohort study - Gong, Chao; Li, Shitong; Huang, Xiaojing; Chen, Lianhua (PeerJ, 2020)
Background Diastolic dysfunction, an early manifestation and clinical symptom of heart failure with preserved ejection fraction, can be influenced by various anesthesia management strategies. Trans-esophageal echocardiography was used to undertake to assess left ventricular diastolic function during anesthesia maintenance using sevoflurane alone and sevoflurane combining with transversus abdominis plane block and rectus sheath block in elderly patients with diastolic dysfunction undergoing abdominopelvic surgery. Methods Thirty-eight patients were divided into two groups in this retrospective study, sevoflurane and sevoflurane combining with TAPB and RSB according to employing different anesthesia maintenance schemes. The parameters HR, MAP, CVP, E, A, E/A, e, a, e/a, and E/a were obtained immediately after anesthesia induction hemodynamics stability (HR1, MAP1, CVP1, E1, A1, E1/A1, e1, a1, e1/a1, and E1/a1) and 1 hour later (HR2, MAP2, CVP2, E2, A2, E2/A2, e2, a2, e2/a2, and E2/a2). Results Transmitral diastolic Doppler flow characteristics illustrated E/A significant decreases in the S group but increases in the ST group (p = 0.02 < 0.05) 1 hour after anesthesia induction hemodynamic stability. Tissue Doppler imaging characteristics showed a more significant increase e/a (P = 0.005 < 0.05) and decreases in a value (p = 0.009 < 0.05) in the ST group 1 hour after anesthesia induction hemodynamics stability. Conclusions Maintaining anesthesia with sevoflurane combining with TAPB and RSB was more suitable for protecting cardiac diastolic function than sevoflurane alone in elderly patients with diastolic dysfunction undergoing open abdominal and pelvic surgery.
Keywords: Diastolic function; Transesophageal echocardiography (TEE); Sevoflurane; Transversus abdominis plane block and rectus sheath block (TAPB and RSB)